Measuring and monitoring soil organic carbon stocks in agricultural lands for climate mitigation. Issue 3 (8th June 2010) - Conant, Richard T; Ogle, Stephen M; Paul, Eldor A; Paustian, Keith
Abstract : Policies that encourage greenhouse‐gas emitters to mitigate emissions through terrestrial carbon (C) offsets – C sequestration in soils or biomass – will promote practices that reduce erosion and build soil fertility, while fostering adaptation to climate change, agricultural development, and rehabilitation of degraded soils. However, none of these benefits will be possible until changes in C stocks can be documented accurately and cost‐effectively. This is particularly challenging when dealing with changes in soil organic C (SOC) stocks. Precise methods for measuring C in soil samples are well established, but spatial variability in the factors that determine SOC stocks makes it difficult to document change. Widespread interest in the benefits of SOC sequestration has brought this issue to the fore in the development of US and international climate policy. Here, we review the challenges to documenting changes in SOC stocks, how policy decisions influence offset documentation requirements, and the benefits and drawbacks of different sampling strategies and extrapolation methods.